(untitled) (Semiárida, 2021)
The objective was to evaluate the response of the specific leaf area (AFE) to different combinations of cutting interval (IC) and cutting height (AC) on tillers cohorts (Co) of Panicum coloratum L. The work was carried out from SeptemberMarch, in greenhouse, on 81 plants grown in PVC pots and distributed in a DCA with factorial arrangement of treatments and repeated measures. The treatments included nine replications of the possible combinations between the IC of 2, 4 and 6 leaves.tiller1 and the AC of 40, 80 and 120 mm for seven cohorts of tillers. In each cut, three tillers were randomly selected per cohort and repetition in which the leaf area (AF) of the penultimate expanded leaf was determined; the leaf blade were dried and weighed to determine their weight (PF) and calculate the AFE. The data were analyzed using ANOVA and the slope and intercept of the relationship between (log10) PF and (log10) AF were estimated, with dummy variables to establish differences between the IC. The variation in AFE as a function of IC was different according to AC (IC×AC interaction; p<0.001) and Co (IC×Co interaction; p<0.004). The slope of the relationship was 1.06, 1.11 and 1.18 (R2=0.97; p<0.001) for the IC of 6, 4 and 2 leaves.tiller1, respectively, higher (p< 0.01) to 1.0 and different (p<0.01) from each other. This indicates that the PF increased faster than the AF as the size of the leaf blade increased. Furthermore, for each unit of increase in AF, the increase in PS was greater with frequent cuts (<IC). However, the ordinate to the origin of 1.46, 1.73 and 2.03 for the IC of 6, 4 and 2 leaves.tiller1 indicates that the decrease in the IC increases the AFE. It is concluded that P. coloratum L. presents phenotypic plasticity to defoliation. This will allow, at least in part, to offset the effect of the decrease in growth due to the removal of the leaf area.